The microwave-assisted ortho-alkylation of azine N-oxides with N-tosylhydrazones catalyzed by copper(i) iodide. Issue 9 (15th December 2015) - Jha, Abadh Kishor; Jain, Nidhi
Abstract : A regioselective direct ortho -alkylation of azine N -oxides has been achieved under ligand-free conditions using copper(i ) iodide and microwave conditions. Abstract : A copper catalyzed regioselective cross-coupling of N -tosylhydrazones with azine N -oxides to yield ortho -alkylated products in moderate to good yields is reported. The reaction is facilitated by microwave, takes place without any ligand, and uses inexpensive copper(i ) iodide as the catalyst.